Inactive Matrix Gla Protein Is Causally Related to Adverse Health Outcomes. Issue 2 (February 2015) - Liu, Yan-Ping; Gu, Yu-Mei; Thijs, Lutgarde; Knapen, Marjo H.J.; Salvi, Erika; Citterio, Lorena; Petit, Thibault; Carpini, Simona Delli; Zhang, Zhenyu; Jacobs, Lotte; Jin, Yu; Barlassina, Cristina; et al.
<x xml:space="preserve">Abstract</x> Matrix Gla-protein is a vitamin K–dependent protein that strongly inhibits arterial calcification. Vitamin K deficiency leads to production of inactive nonphosphorylated and uncarboxylated matrix Gla protein (dp–ucMGP). The risk associated with dp–ucMGP in the population is unknown. In a Flemish population study, we measured circulating dp–ucMGP at baseline (1996–2011), genotyped MGP, recorded adverse health outcomes until December 31, 2012, and assessed the multivariable-adjusted associations of adverse health outcomes with dp–ucMGP. We applied a Mendelian randomization analysis using MGP genotypes as instrumental variables. Among 2318 participants, baseline dp–ucMGP averaged 3.61 μg/L. Over 14.1 years (median), 197 deaths occurred, 58 from cancer and 70 from cardiovascular disease; 85 participants experienced a coronary event. The risk of death and non-cancer mortality curvilinearly increased (P⩽0.008) by 15.0% (95% confidence interval, 6.9–25.3) and by 21.5% (11.1–32.9) for a doubling of the nadir (1.43 and 0.97 μg/L, respectively). With higher dp–ucMGP, cardiovascular mortality log-linearly increased (hazard ratio for dp–ucMGP doubling, 1.14 [1.01–1.28]; P=0.027), but coronary events log-linearly decreased (0.93 [0.88–0.99]; P=0.021). dp–ucMGP levels were associated (P⩽0.001) with MGP variants rs2098435, rs4236, and rs2430692. For non-cancer mortality and coronary events (P⩽0.022), but not for total and cardiovascular mortality (P≥0.13), the Mendelian randomization analysis suggested causality. Higher dp–ucMGP predicts total, non-cancer and cardiovascular mortality, but lower coronary risk. For non-cancer mortality and coronary events, these associations are likely causal.